Will the expanded audit report model proposed by IAASB reduce the expectation gap in South Africa? - Maseko, Kwena Nicholas (My University, 2016)
In 2013 the International Auditing and Assurance Standards Board (IAASB) proposed the revision of the international auditing standard on the audit report (ISA 700) to meet the information needs of the users of audited financial statements. The purpose of this research was to investigate whether the International Standards Assurance and Accounting Board’s (IAASB) revised International Standard on Auditing (ISA 700) would reduce the expectation gap. It focused on the expectation gap investigation in three areas, namely: responsibilities of auditors, reliability of audited financial statements and decision-making usefulness of audited financial statements. A differential testing instrument was used in the study and completed by research subjects that comprised auditors, bankers and shareholders. Non-parametric Kruskal-Wallis H test and non-parametric Mann-Whitney test were used to analyse the data. The results of the study showed that despite the audit report modifications, expectation gap remained persistent with regard to auditors’ responsibilities. On the positive front, the study showed that the revised ISA 700 resulted in users finding audited financial statements reliable and useful for decision-making purposes.
Keywords: Auditing standards; South Africa